Association between inflammatory cytokines and symptoms of major depressive disorder in adults - Min, Xue; Wang, Genwei; Cui, Yalian; Meng, Peipei; Hu, Xiaodong; Liu, Sha; Wang, Yanfang (Frontiers in Immunology, 2023)
Objective This study investigated the association of Inflammatory cytokines and major depressive disorder. Methods Plasma biomarkers were measured by enzyme-linked immunosorbent assay (ELISA). Spearman analysis was performed to correlate the biomarkers with the total score and score reduction rate of the 17-item Hamilton Depression Rating Scale (HAMD-17). Receiver operator characteristic (ROC) curve were analyzed for the effect of biomarkers on major depression disorder (MDD) and healty controls (HC) classification and diagnosis. Results The levels of tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6) in the MDD group were significantly higher than the HC group, and the levels of high mobility group protein 1 (HMGB1) were significantly lower than the HC group. The ROC curves showed that the AUCs of HMGB1, TNF-α, and IL-6 were 0.625,0.733, and 0.783, respectively. The levels of brain-derived neurotrophic factor precursor (PROBDNF) levels were positively correlated with the total HAMD-17 score in male MDD patients, and brain-derived neurotrophic factor (BDNF) and interleukin 18 (IL-18) levels were negatively correlated with the total HAMD-17 score in female MDD patients. Conclusion Inflammatory cytokines are associated with the symptoms of major depressive disorder, and HMGB1, TNF-α, and IL-6 have potential as objective biomarkers to aid in the diagnosis of MDD.